So What’s My Part? Collective Duties, Individual Contributions, and Distributive Justice - Schulz, Moritz (Historical Social Research-Historische Sozialforschung, 2023)
Problems in normative ethics paradigmatically concern what it is obligatory or permissible for an individual to do. Yet sometimes, each of us ought to do something individually in virtue of what we ought to do together. Unfortunately, traversing these two different levels at which a moral obligation can arise – individual and collective – is fraught with difficulties that easily lure us into conclusions muddying our understanding of collective obligations. This paper seeks to clearly lay out a systematic problem central to the relation between collective and individual duties in view of alleviating some such confusion and facilitating more concerted attempts at resolving it: Collective duties require individuals to act in order for the collective duty to be fulfilled. Yet typically, a collective duty does not entail any one set of individual duties that would prescribe such contributory actions: The work we need to do in order to fulfil a duty can be allocated differently to the individuals collectively bearing it. Much like in matters of distributive justice, then, deriving individual duties from a collective one requires us to employ a distributive scheme, which raises separate normative concerns that have rarely taken centre stage in the debate so far.<br
Keywords: collective duties; collective obligations; distributive justice